Nothing to sleep upon - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Integrating the sterile insect technique as a key component of area-wide tsetse and trypanosomiasis intervention PAAT Technical and Scientific Series, FAO, 2001. 76 pp. ISBN 9251046468 US$ 8 Euro 8.10